Kesalahan Siswa dalam Menyelesaikan Soal Uraian pada Materi Operasi Hitung Bilangan Bulat di Kelas V SD Negeri 88 Kota Bengkulu - arieska, sarlin; rahimah, dewi; muchlis, effie efrida (JP2MS, 2018)
This study aims to find out the mistake of students in solving math problems on the material integer arithmetic operations. This research is a descriptive research. The subjects were 25 students of class V SDN 88 Bengkulu City Odd Semester Academic Year 2017/2018. Data collection techniques used in this research that tests. Analysis of the data in this study was done descriptively. The results showed the students make the mistake of using the basic competence to determine the prime factors the Commission and the FPB, and resolve issues related to arithmetic operations, the Commission and the FPB, based on indicators: (1)Using the prime factors and prime factorization to solve everyday problems associated with the FPB in even numbers as much as 6 students, (2) using the prime factors and prime factorization to solve everyday problems associated with the FPB in an even number and odd as many as 15 students (3) Using the prime factors and prime factorization to solve everyday problems associated with the Commission on an even number as many as 14 students, (4) Using the prime factors and prime factorization to solve everyday problems associated with the Commission on an even number and odd as many as 18 students, (5a) Solve problems related to the FPB as many as 25 students, (5b) Solve problems related to the FPB as many as 24 students, (6a) Solve problems related to the Commission by 24 students,and (6b) Solve the problems associated with the Commission as many as 23 students.